2008
DOI: 10.1243/13506501jet390
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of hydromagnetic squeeze films between two conducting rough porous circular plates

Abstract: In this paper, the problem of squeeze films between electrically conducting rough porous surfaces and electrically conducting lubricant in the presence of transverse magnetic field is investigated for circular shape of the bearing surfaces. The bearing surfaces are assumed to be transversely rough. The roughness of the bearing surface is modelled by a stochastic random variable with non-zero mean, variance, and skewness. The associated Reynolds equation is stochastically averaged with respect to the random rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It is easily observed that the dimensionless pressure distribution in the bearing system given by equation (18) and equation (21) while the non dimensional load carrying capacity of the bearing system is obtained from equation (20) and equation (22). It is clearly seen that the pressure increases by…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is easily observed that the dimensionless pressure distribution in the bearing system given by equation (18) and equation (21) while the non dimensional load carrying capacity of the bearing system is obtained from equation (20) and equation (22). It is clearly seen that the pressure increases by…”
Section: Resultsmentioning
confidence: 98%
“…[19] analyzed the effect of magneto-hydrodynamic squeeze film characteristics between curved annular plates. On the basis of the Christenson and Tonder's stochastic model of roughness, the discussion carried out by [20][21][22][23] reported that the negatively skewed roughness turns in better performance. All these above studies established that increasing values of porosity caused reduced load carrying capacity and friction.…”
Section: Introductionmentioning
confidence: 99%
“…The representation for dimensionless pressure profile is given in (11) while the nondimensional load bearing capacity is governed by (12). From these equations it is clearly observed that the load carrying capacity…”
Section: Resultsmentioning
confidence: 99%
“…The hydromagnetic squeeze films between two conducting rough circular plates are studied by Vadher et al [12]. It was investigated that the negative effect of roughness got minimized up to some extent by applying magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…It was noticed that the squeeze film characteristics got enhanced for transverse roughness whereas the bearing suffered owing to the existence of longitudinal roughness pattern. Vadher et al (2008) considered the problem of squeeze films between electrically conducting rough porous surfaces and electrically conducting lubricant in the presence of a transverse roughness for a circular shape of the bearing surfaces. The negative influence of transverse surfaces roughness was reduced due to magnetization.…”
Section: Introductionmentioning
confidence: 99%